Substrate switches, phenotypic innovations and allopatric speciation formed taxonomic diversity within the lichen genus Blastenia. Issue 3 (28th August 2019) - Vondrák, Jan; Frolov, Ivan; Košnar, Jiří; Arup, Ulf; Veselská, Tereza; Halıcı, Gökhan; Malíček, Jiří; Søchting, Ulrik
Abstract: Blastenia is a widely distributed lichen genus in Teloschistaceae. We reconstructed its phylogeny in order to test species delimitation and to find evolutionary drivers forming recent Blastenia diversity. The origin of Blastenia is dated to the early Tertiary period, but later diversification events are distinctly younger. We recognized 24 species (plus 2 subspecies) within 6 infrageneric groups. Each species strongly prefers a single type of substrate (17 species occur on organic substrates, 7 on siliceous rock), and most infrageneric groups also show a clear substrate preference. All infrageneric groups tend to have the Mediterranean and Macaronesian distribution, but some epiphytic species have much larger geographic ranges and some evolved after a long‐distance dispersal outside the region. Chlorinated and nonchlorinated anthraquinone chemosyndromes co‐occur in apothecia of most species, but the chemotype has been secondarily reduced in some lineages. One infrageneric group has a marked reduction in apothecial size, associated with a substrate shift to twigs. Only seven species have vegetative diaspores; they also produce apothecia but have smaller ascospores. Genome sizes (22‐35 Mb in Blastenia ) are significantly higher in epilithic species. Within‐species genetic variation is low in widely distributed species but high in some epilithic species with small geographical ranges. New taxa are: B. afroalpina, B. anatolica, B. caucasica, B. gennargentuae, B. herbidella subsp. acidophila, B. lauri, B. monticola, B. palmae, B. psychrophila, B. purpurea, B. relicta, B. remota, B. xerothermica, and B. xerothermica subsp. macaronesica . New combinations are: B. festivella and B. subathallina ; both names and B. catalinae are lectotypified.